Sistema de señalización inteligente para estaciones del sistema integrado de transporte urbano (SITU) de la ciudad de Loja - Hurtado Torres, Geovanny Israel (2018)
A city is part of the Smart City concept, due to the tendency to use information technologies, which aim to automate and improve the services that people access to. Within these services, urban transport is considered one of the factors, and for this reason the signage of this means of mobilization is emphasized. The design of intelligent signage is presented in an audiovisual way, which is located at the stop and in the transport unit, which together with the technological instruments facilitate the mobilization of people through public transport. The way of operating the system is through wireless connection, where as the mobile unit approaches the stop, it is identified in the device located at the stop, informing the travel route of the transportation unit, and at the same time, in the mobile unit or bus, it gives the notice of the station where it arrives and the next one in the path; helping to encourage people to access and use this means of transport. Similarly, a database is managed in order to control and observe the performance regarding the travel time of the transportation unit. Therefore, all these aspects contribute to improve and guarantee a mass access service.